De l’euphorie comme modalité du connaître dans le soin - Natalie Rigaux (Revue d'anthropologie des connaissances)
Based on an ethnographic study conducted over seven years (from 2011 to 2018) on home care for people with dementia, we will follow the thread of euphoria in order to explore, from a pragmatist perspective, how emotion and cognition, body and language, in a reflexive or narrative mode, intertwine to enable knowledge of care envisaged as an “experience” in the sense in which J. Dewey understands it. Two very distinct contexts will enable us to identify two modes of producing knowledge about care: the first relates to times when care is given and received, which we will examine by focusing on the experience of the person being cared for; the second concerns moments when carers elaborate on their practice and its difficulties at a distance from care (team meetings, discussion groups, intervision).